Let's talk about mucormycosis emergency with COVID-19: Invest in future - Kamlesh Malik; Jyoti Arora; Parvin K Yadav; Kusum K Rohilla (Journal of Family Medicine and Primary Care, 2022)
Despite recent breakthroughs in the detection and treatment during the COVID-19 pandemic, mucormycosis is a serious infection with a high death rate. It is a filamentous fungal infection from the zygomycetes class of order mucorales. It is a fatal fungal infection with a 50% or higher overall fatality rate. Mucormycosis is a fungal infection caused by mucor, which is a mold that can be found in soil, rotting fruits, and vegetables. It can primarily affect the brain, lungs, and sinuses. It is very much fatal in patients with diabetes or who are highly immunocompromised such as patients with cancer. In addition to more than 50% mortality rate, surgical intervention may require necrotic tissue removal, which leads to severely disfiguring surgery.